2020
DOI: 10.1515/nanoph-2020-0237
|View full text |Cite
|
Sign up to set email alerts
|

Dual-polarized multiplexed meta-holograms utilizing coding metasurface

Abstract: AbstractIn this paper, a novel method is proposed to achieve two distinct information channels by simultaneously manipulating both the transmitted cross- and co-polarized components of a 1-bit coding metasurface under linearly polarized incidence. Compared to previously demonstrated incidence-switchable or position multiplexed holograms, our proposed coding meta-hologram can simultaneously project two independent holographic images without inevitable change of the incidence sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 60 publications
(75 reference statements)
0
38
0
Order By: Relevance
“…Polarization multiplexed metasurface holograms are sensitive to the incident polarization state, and different holographic images can be reconstructed by changing the incident wave polarization. For the transmission-type metasurface [110], the coding metasurface holographic can project two independent holographic images at the same time under a unique linearly polarized incidence, while avoiding crosstalk between the two different channels. The metasurface is composed of double-layer split-ring sub-wavelength elements, and the orientation of the double-layer split-ring aperture is specially designed to be 45 • or 135 • .…”
Section: Polarization-multiplexed Metasurface Hologramsmentioning
confidence: 99%
“…Polarization multiplexed metasurface holograms are sensitive to the incident polarization state, and different holographic images can be reconstructed by changing the incident wave polarization. For the transmission-type metasurface [110], the coding metasurface holographic can project two independent holographic images at the same time under a unique linearly polarized incidence, while avoiding crosstalk between the two different channels. The metasurface is composed of double-layer split-ring sub-wavelength elements, and the orientation of the double-layer split-ring aperture is specially designed to be 45 • or 135 • .…”
Section: Polarization-multiplexed Metasurface Hologramsmentioning
confidence: 99%
“…Metasurfaces that are considered the artificial ultrathin planar metamaterials, composed of periodic subwavelength unit cells arranged in specific sequences [21][22][23], have attracted much attention as a result of their exotic properties [24,25]. The unit cells of the metasurfaces have been engineered to flexibly manipulate the electromagnetic wave propagations [22], leading to a plethora of applications that range from polarization control [26,27], perfect absorption/transmission [28], and spectral responses [29,30]. Recently, it has already been demonstrated that the operation frequency of the metasurfaces can be extended from microwaves to optical frequencies owing to their unique abilities to provide efficient control over the amplitude, phase, and polarization of the local fields [22,31].…”
Section: Introductionmentioning
confidence: 99%
“…Multiplexing encrypted holography, which splits and stores information in different channels, has recently received considerable interest due to its excellent ability to store/display information securely. The proposed encryption technology mainly focuses on the polarization, spin or wavelength multiplexing, [35][36][37] chemical or physical switching, [38,39] near-far field conversion, [40] nonlinear responses, [36,[41][42][43] asymmetric polarization encryption, [44][45][46] and so on. Among these encryption methods, polarization multiplex encryption is considered to be prominent due to its large degree of freedom and possible numerous design schemes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 55 ] For linearly polarized incidences, the scattered cross‐polarized components can be controlled using only geometric phase metasurface, [ 52 ] while the unit cell structure parametric variation (propagation phase) is a must for the manipulation of the co‐polarization response. [ 35,37,56 ] Simultaneous independent manipulation of the co‐polarization and cross‐polarization components can be realized by further adding geometric phase to the propagation phase. [ 35 ] In polarization multiplexing technology, geometric phase based on the P–B phase principle is generally exploited to manipulate the cross‐polarization response, and propagation phase is adopted to manipulate the co‐polarization response.…”
Section: Introductionmentioning
confidence: 99%